(untitled) (المجلة الدولية للبحوث العلمية, 2024)
Factors affecting the political news journalists in the Sudanese newspaper organizations when they are doing their duties. This study is a descriptive research study designed to obtain pertinent and precise information concerning the status of the phenomena, and, whenever possible, to draw valid general conclusions from the facts discovered. questionnaire was used as a tool for this study. samples were chosen from journalists working in the Sudanese newspaper institutions, representing, an intended sample from the field study community. The descriptive method is used to describe the situation and analysis of the results: The study proved that male journalists worked in the political news sections, more than female, are working in the same sections, and the paid wages to the various categories of the journalists in the Sudanese newspaper situations, are unsuitable for the effort exerted in their working. The study shows that political Sudanese journalist is subjected to pressure when they are doing their duties.